Pengaruh Kompetensi Guru terhadap Pengetahuan Siswa dan Minat Menabung Siswa di Bank Mini Sekolah - Akmal Akmal; Novela Juliana (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2023)
TThe low interest in saving students at SMK Muhammadiyah 2 Pekanbaru at the Mini School Bank raises several hypotheses regarding knowledge of financial literacy, interest in saving and the influence of teacher competence. The purpose of this study was to determine the effect of teacher competence in increasing students' financial literacy knowledge at SMK Muhammadiyah 2 Pekanbaru. As well as the indirect effect of teacher competence on interest in saving through students' financial literacy knowledge at the Mini School Bank of SMK Muhammadiyah 2 Pekanbaru. The method in this research is to use a quantitative descriptive approach. The results of this study are that there is a significant effect of teacher competence on students' financial literacy knowledge at SMK Muhammadiyah 2 Pekanbaru, there is an indirect effect of teacher competence on interest in saving through students' financial literacy knowledge at SMK Muhammadiyah 2 Pekanbaru. The conclusion of this study is that the hypothesis in this study is accepted